Republic of Kazakhstan : 2011 Article IV Consultation; Staff Report; Supplement; and Public Information Notice. (IMF Staff Country Reports; Country Report ;, 2011)
Kazakhstan's economic recovery and unemployment rate and other issues are discussed in this paper. The banking and corporate sectors have not recovered from the crisis despite strong economic growth. Ownership and partial financing of the envisaged centralized distressed asset fund by the National Bank of Kazakhstan (NBK) poses risks to the integrity of monetary policy, and may create conflicts with its new supervisory powers. The importance of fully implementing the announced macroprudential measures and enhancing liquidity management practices to manage a possible increase in capital inflows are outlined.